Menghadapi Badai Digital: Media Sosial dan Keberhasilan Manajemen Krisis Dough Lab - Indrabudi, Bintang Ramasalsa; Ayuningtyas, Fitria (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
This study analyzes the role of social media in reputation crisis management at Dough Lab following a viral incident related to product cleanliness that damaged the company’s image. The case began with a viral video showing a rat in a Dough Lab store, which spread widely on social media and tarnished the company’s reputation. Using a qualitative approach with a case study method, this research explores how Dough Lab utilized social media to respond to the crisis, provide clarification, and restore its reputation. Data were collected through content analysis of official statements on social media and responses from netizens. The findings show that quick response, transparency, and open communication played a crucial role in mitigating the crisis, improving the company’s image, and accelerating reputation recovery through social media.